Integrating sex and gender into neurodegeneration research: A six‐component strategy. Issue 4 (22nd November 2017) - Tierney, Mary C.; Curtis, Ashley F.; Chertkow, Howard; Rylett, R. Jane
Abstract: Introduction: Despite important sex differences, there remains a paucity of studies examining sex and gender differences in neurodegeneration. The Canadian Consortium on Neurodegeneration in Aging (CCNA), a national network of researchers, provides an ideal platform to incorporate sex and gender. Methods: CCNA's Women, Gender, Sex and Dementia program developed and implemented a six‐component strategy involving executive oversight, training, research collaboration, progress report assessment, results dissemination, and ongoing manuscript review. The inclusion of sex and gender in current and planned CCNA projects was examined in two progress reporting periods in 2016. Results: Sex and gender research productivity increased substantially for both preclinical (36%–45%) and human (56%–60%) cohorts. The main barrier was lack of funding. Discussion: The Women, Gender, Sex and Dementia strategy resulted in a major increase of sex and gender into research on neurodegenerative disorders. This best practice model could be utilized by a wide variety of large multidisciplinary groups. Highlights: There is a paucity of research on sex and gender in neurodegenerative disorders. A six‐component strategy to integrate sex and gender into research was developed. Strategy implemented in national network of researchers studying neurodegeneration. Sex and gender research productivity increased for preclinical and human research. Strategy could be adapted and utilized across various multidisciplinary groups.